Desarrollo del rango de movimiento articular, capacidades coordinativas y aptitud física en niñas rusas de 5 a 6 años practicantes de gimnasia rítmica. Estudio transversal (Development of range of motion articular, coordinative abilities, and physical fitness in russian girls aged 5 to 6 practicing rhythmic gymnastics: a cross-sectional study) - Polevoy, Georgiy; Fuentes-Barría, Héctor (Retos, 2024)
Objetivo: Evaluar la efectividad de los medios y métodos utilizados para desarrollar la movilidad articular, capacidades coordinativas y aptitud física en niñas rusas de entre 5 a 6 años practicantes de gimnasia rítmica. Material y Métodos: Estudio transversal realizado en la Escuela Deportiva No. 1 de Kirov (Rusia) entre noviembre de 2022 y febrero de 2023. Participaron 30 niñas evaluadas en movilidad articular (Split, Twist y Bridge), capacidades coordinativas (Single Leg Standing Balance, "Figure of 8 Walk y Lying Wall Squat), y aptitud física (Long Jump Two Legs, 20-meter Sprint y Hanging on Bent Arms). Se utilizó la prueba t de Student y el coeficiente de correlación de Pearson para el análisis estadístico. Resultados: La movilidad coxofemoral disminuyó significativamente (p = 0,01; d = 0,21). El balance postural y la coordinación muscular mejoraron significativamente (p = 0,03 y p = 0,02, respectivamente; d = 0,2), y la fuerza isométrica aumentó (p = 0,02; d = 17,2). Se halló una asociación entre el Single Leg Standing Balance, Split y "Hanging on Bent Arms (r = 0,4; p = 0,03), y entre Wall Squat y "Bridge" (r = 0,4; p = 0,03). Conclusión: Hubo una pérdida en la movilidad coxofemoral y mejoras en balance postural y coordinación en niñas de 5 a 6 años, destacando la importancia de considerar las fases sensibles para el desarrollo físico y el estado madurativo del sistema neuromuscular. Palabras clave: Rango de Movimiento Articular; Actividad motora; Desempeño atlético; Gimnasia; Niña. Abstract. Objective: To evaluate the effectiveness of the means and methods used to develop joint mobility, coordinative abilities, and physical fitness in Russian girls aged 5 to 6 practicing rhythmic gymnastics. Material and Methods: A cross-sectional study conducted at Sports School No. 1 in Kirov (Russia) from November 2022 to February 2023. Thirty girls were assessed for joint mobility (Split, Twist, and Bridge), coordination skills (Single Leg Standing Balance, Figure of 8 Walk, and Lying Wall Squat), and physical fitness (Long Jump Two Legs, 20-meter Sprint, and Hanging on Bent Arms). Statistical analysis employed Student’s t-test and Pearson’s correlation coefficient. Results: Coxofemoral mobility decreased significantly (p = 0.01; d = 0.21). Postural balance and muscular coordination improved significantly (p = 0.03 and p = 0.02, respectively; d = 0.2), and isometric strength increased (p = 0.02; d = 17.2). Associations were found between Single Leg Standing Balance, Split, and Hanging on Bent Arms (r = 0.4; p = 0.03), and between Wall Squat and Bridge (r = 0.4; p = 0.03). Conclusion: There was a loss in coxofemoral mobility and improvements in postural balance and coordination in 5 to 6-year-old girls, highlighting the importance of considering sensitive periods for physical development and the maturational state of the neuromuscular system. Keywords: Range of Motion, Articular; Motor Activity; Athletic Performance; Gymnastics; Child.